Waist circumference mediates the relationship between atherogenic index of plasma and infertility - Wei, Xue; Liu, Dandan (Frontiers in Endocrinology, 2025)
BackgroundA newly developed technique, Atherogenic Index of Plasma (AIP), is linked to numerous metabolic disorders. Prior researches have indicated strong correlation between AIP and waist circumference (WC), as well as between WC and infertility. Yet no investigation has examined link involving the AIP and infertility, as well as the potential mediating role of WC in this relationship.MethodsThe study included 1,322 women from the 2013–2018 NHANES. Infertility was the outcome variable. Moreover, mediation analysis explored the mediating role of WC in the above relationships.ResultsThere were 1,163 controls and 159 infertile participants among the 1,322 participants. The study demonstrated increased WC and elevated AIP among infertile women. Also, the AIP demonstrated an independent correlation with a higher likelihood of infertility, regardless of adjustments for confounding factors. Subgroup analysis indicated the AIP was related to the prevalence of infertility even among women aged 35 years or younger with no history of cardiovascular disease (CVD), pelvic infections, or use of female hormones. Finally, WC had a substantial mediating effect on correlation between AIP and infertility, accounting for 54.49% of the association. Yet, it appears that the various IR surrogates did not demonstrate variability in their predictive ability for infertility [AIP: 0.642 (95% CI: 0.599, 0.683) vs. WC 0.658 (95% CI: 0.618, 0.705) vs. HOMA-IR 0.637 (95% CI: 0.593, 0.686)].ConclusionA notable positive correlation exists between AIP and female infertility. It provides the first evidence to demonstrate the mediating role of WC in the above relationship. Managing abdominal obesity and monitoring AIP levels may contribute to reduce the likelihood of infertility.